2018
DOI: 10.1111/1460-6984.12363
|View full text |Cite
|
Sign up to set email alerts
|

Tense and plural formation in Welsh–English bilingual children with and without language impairment

Abstract: By focusing on aspects of morphosyntactic development which are unique to Welsh, we have increased existing about how verbal and nominal morphology are acquired in Welsh-speaking bi-SLI and bi-TD children. The present results point towards productivity problems for Welsh-speaking bi-SLI children who are adversely influenced by low-frequency structures and fail to over-regularize in the context of verbal and nominal concatenating morphology. From a clinical perspective, targeting synthetic past-tense forms thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 66 publications
(180 reference statements)
0
15
0
Order By: Relevance
“…The second type of past tense structure is less frequent in spoken language but conforms to the typical VSO word order, consisting of the lexical verb with an attached past tense inflection, followed by the subject and the object (e.g., the Welsh equivalent of see‐ PAST girl dog ‘the girl saw the dog’). Chondrogianni and John () tested Welsh–English bilingual children with DLD and age controls on both types of past tense. Although the children with DLD were less accurate than their age mates on both types, the difference was especially striking for items requiring the use of lexical verbs inflected for past tense.…”
Section: Factor 1: the Allure Of Bare Stemsmentioning
confidence: 99%
“…The second type of past tense structure is less frequent in spoken language but conforms to the typical VSO word order, consisting of the lexical verb with an attached past tense inflection, followed by the subject and the object (e.g., the Welsh equivalent of see‐ PAST girl dog ‘the girl saw the dog’). Chondrogianni and John () tested Welsh–English bilingual children with DLD and age controls on both types of past tense. Although the children with DLD were less accurate than their age mates on both types, the difference was especially striking for items requiring the use of lexical verbs inflected for past tense.…”
Section: Factor 1: the Allure Of Bare Stemsmentioning
confidence: 99%
“…At the same time, the lack of L2 English instruction may place the L2-SLI children in our study at a disadvantage compared to the SLI children in the Canadian study for reasons mentioned above. Moreover, the Welsh-English L2-SLI children in our study also had problems with concatenating morphology in their L1 (Chondrogianni & John, 2018). It seems, thus, that the problems with productive morphology that the L2-SLI_Y children face in their L1 transfer to their L2 (English) and may be accentuated by the lack of intense and lengthy L2 exposure.…”
Section: Tense and Agreement In Young L2-sli Childrenmentioning
confidence: 53%
“…To date, the study by Chondrogianni and John (2018) is the only one to experimentally investigate how tense develops in the L1 Welsh of the same young Welsh-English bilingual children with TLD and SLI also reported here. The authors reported that Welsh-speaking L1-English L2-TLD children had almost ceiling accuracy in the periphrastic form of the past tense and were successfully prompted to produce the less frequent synthetic form of the past tense.…”
Section: Tense In English and Welshmentioning
confidence: 84%
See 2 more Smart Citations